The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1413-86702006000500014
|View full text |Cite
|
Sign up to set email alerts
|

Congenital tuberculosis: a case report

Abstract: Congenital tuberculosis is an unusual and severe clinical pattern of tuberculosis presentation of Mycobacterium tuberculosis infection. Furthermore, it usually has a difficult treatment. We report a two-month-old male infant who presented with fever, dyspnea and a diffuse micronodular pattern at x-ray; mother with severe tuberculosis. Treatment with the triple drug regimen was initiated, but the child developed jaundice and an increase in liver enzymes on various occasions during treatment. A regimen specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…In the review of 75 congenital TB cases (see Methods) we found that information on maternal TB was available in 65; 43 had chest radiograph results. Of these 43, 14 (33%) had a normal chest radiograph with confirmed extrapulmonary TB, 12 (28%) had pleural effusions of whom six also had other pulmonary infiltrates (only one culture‐positive), eight (19%) had miliary TB and 10 (23%) had only pulmonary TB, most of which was culture‐negative TB 6–43 . Other types of extrapulmonary TB identified in these mothers were endometrial TB confirmed in 22 of 25 tested, central nervous system TB in six, osteoarticular and abdominal TB in three each.…”
Section: Tuberculosis In the Very Youngmentioning
confidence: 98%
See 1 more Smart Citation
“…In the review of 75 congenital TB cases (see Methods) we found that information on maternal TB was available in 65; 43 had chest radiograph results. Of these 43, 14 (33%) had a normal chest radiograph with confirmed extrapulmonary TB, 12 (28%) had pleural effusions of whom six also had other pulmonary infiltrates (only one culture‐positive), eight (19%) had miliary TB and 10 (23%) had only pulmonary TB, most of which was culture‐negative TB 6–43 . Other types of extrapulmonary TB identified in these mothers were endometrial TB confirmed in 22 of 25 tested, central nervous system TB in six, osteoarticular and abdominal TB in three each.…”
Section: Tuberculosis In the Very Youngmentioning
confidence: 98%
“…The clinical presentation of congenital TB in the review of 75 cases is summarized in Table 1 6–43 . Although postnatal TB may clinically be indistinguishable from congenital TB, the presence of a hepatic granuloma is fairly pathognomic of congenital TB 9 .…”
Section: Tuberculosis In the Very Youngmentioning
confidence: 99%
“…The incidence of congenital tuberculosis in women of reproductive age group in countries where the disease is endemic is estimated at 2%,1 with approximately 340 cases described in the literature 2. Diagnosis of congenital tuberculosis is difficult due to non-specific symptoms, and a high index of suspicion is required for early diagnosis in infants in order to reduce mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical manifestations of congenital and neonatal TB are non-specific, they usually present like neonatal sepsis and diagnosis is often delayed [15–18]. Low birth weight and prematurity are common features of HIV and TB infected neonates born to HIV-infected mothers with TB [19].…”
Section: Casementioning
confidence: 99%
“…These criteria increase diagnostic sensitivity, but the diagnosis remains difficult since confirmation of the primary complex or detection of granulomas in the liver has to be carried out by biopsy, which is not always available [20]. In our case a liver biopsy was never performed [15]. …”
Section: Casementioning
confidence: 99%